Growing up Filipino 3 new stories for young adults - Brainard, Cecilia Manguerra 1947- (Manila, Philippines University of Santo Tomas Publishing House, 2022)
Collects 25 short stories by Filipino authors in the US and the Philippines about what it means to be young and Filipino. The stories explore the universal themes of coming-of-age, love, angst, family, relationships, and other young adult issues. The stories reveal Filipino and Filipino American culture, mores, history, society, politics, and other nuances. For instance, Filipino respect for their elders, extended families, religious practices, funereal rites, love for folklore are apparent in the stories. GROWING UP FILIPINO 3: NEW STORIES FOR YOUNG ADULTS follows two earlier critically acclaimed books. --Provided by publisher.
Introduction / Cecilia Manguerra Brainard -- Tall Woman from Leyte / Gona Apostol -- Let Me Tell You About My Aunt Edelweiss / Kannika Claudine D. Pena -- The Fancy Dancer / John Jack G. Wigley -- Beauty Queens / Veronica Montes -- Lola Ging and the Crispa Redmanizers / Nikki Alfar -- Zombie Queen / Yvette Fernandez -- The Kite / Danton Remoto -- The Dead Boy / Cecilia Manguerra Brainard -- The Child / George Gonzaga Deoso -- Pig / Patricia Manuel Go -- Becoming Victoria / Migs Bravo Dutt -- The Rubber Duckie Confessions / Ian Rosales Casocot -- The Goat / James M. Fajarito -- Nilda / Angelo R. Lacuesta -- Then Cruel Quiet / Dominic Sy -- Negros / Eileen R. Tabios -- Narisa / Marianne Villanueva -- It's Cold in America!! / Marilyn C. Alquizola -- Refugees: 1980 / Brian Ascalon Roley -- Dress Down Day / Patrick Joseph Caoile -- Kalihi in Farrah / R. Zamora Linmark -- Happy / Linda Ty-Casper -- Pigeons for Ethel / Renee Macalino Rutledge -- The Secret / Noelle Q. de Jesus -- Babaylan in Playland / Oscar Penaranda.
Ages 13 and older.
Grades 10-12.
Keywords: Young adult fiction, Philippine (English)